Construction of 6-thioguanine and 6-mercaptopurine carriers based on βcyclodextrins and gold nanoparticles. (1st December 2017) - Sierpe, R.; Noyong, Michael; Simon, Ulrich; Aguayo, D.; Huerta, J.; Kogan, Marcelo J.; Yutronic, N.
Highlights: βcyclodextrins with 6-thioguanine and 6-mercaptopurine inclusion complexes. Formation of ternary systems βcyclodextrin – drug – gold nanoparticles. New nanosystems with potential use in transport of antitumour drugs. Abstract: As a novel strategy to overcome some of the therapeutic disadvantages of 6-thioguanine (TG) and 6-mercaptopurine (MP), we propose the inclusion of these drugs in βcyclodextrin (βCD) to form the complexes βCD-TG and βCD-MP, followed by subsequent interaction with gold nanoparticles (AuNPs), generating the ternary systems: βCD-TG-AuNPs and βCD-MP-AuNPs. This modification increased their solubility and improved their stability, betting by a site-specific transport due to their nanometric dimensions, among other advantages. The formation of the complexes was confirmed using powder X-ray diffraction, thermogravimetric analysis and one and two-dimensional NMR. A theoretical study using DFT and molecular modelling was conducted to obtain the more stable tautomeric species of TG and MP in solution and confirm the proposed inclusion geometries. The deposition of AuNPs onto βCD-TG and βCD-MP via sputtering was confirmed by UV–vis spectroscopy. Subsequently, the ternary systems were characterized by TEM, FE-SEM and EDX to directly observe the deposited AuNPs and evaluate their sizes, size dispersion, and composition. Finally, the in vitro permeability of the ternary systems was studied using parallel artificial membrane permeability assay (PAMPA).